Genotype I Newcastle Disease Virus, Isolated from Wild Duck, Can Protect Chickens Against Newcastle Disease Caused by Genotype VII - Elizaveta Boravleva; Anastasia Treshchalina; Daria Gordeeva; Alexandra Gambaryan; Alla Belyakova; Irina Gafarova; Alexey Prilipov; Galina Sadykova; Simone Adams; Tatiana Timofeeva; Natalia Lomakina (Pathogens)
Newcastle disease viruses (NDVs) circulating among wild birds and poultry may differ in virulence. Some NDVs cause devastating outbreaks in chickens. The NDV/duck/Moscow/3639/2008 (d3639) strain was isolated from a wild duck. Its genome was sequenced (PP795281, GenBank) and the biological properties, specifically for infection in chicken and mice, were studied. Strain d3639 of genotype I.2 has an F protein cleavage site (112-GKQGRL-117) and a HN protein length (616 a.a.) of the lentogenic pathotype. It was tested, in comparison with the genotype II LaSota vaccine strain, for its immunogenicity and protective efficacy against a challenge with the velogenic NDV strain NDV/chicken/Moscow/6081/2022 (ch6081) of sub-genotype VII.1.1, the complete genome of which was also sequenced in this study (PP766718, GenBank). Both the d3639 and LaSota viruses did not induce clinical signs in chickens or mice. Single immunization was performed by inoculation through drinking water with the live virus. Inoculation protected the chickens during a subsequent challenge with velogenic ch6081 and significantly reduced shedding in feces. Double immunization was sufficient to achieve prolonged immunity and prevented the shedding of the velogenic virus after the challenge. Thus, this natural lentogenic d3639 virus possesses properties similar to the LaSota vaccine strain and can protect against sub-genotype VII.1.1 NDV.